1998
DOI: 10.1038/sj.onc.1202056
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of protein kinase A is not required for c-mos translation during meiotic maturation of Xenopus oocytes

Abstract: It has been shown previously that protein kinase A (PKA) maintains Xenopus oocytes arrested at G2, at least in part by preventing c-mos translation, but how PKA controls c-mos translation is not known. Using microinjection of recombinant c-mos, which still activates MAP kinase in the presence of active PKA, we have found that PKA does not exert any e ect on translation of endogenous c-mos if MAP kinase is ®rst activated. Even though they accumulate c-mos and contain MAP kinase activity as high as control oocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…The hormone, therefore, triggers cyclin B1 accumulation by acting through a decrease in PKA activity (Figure 10). This again differentiates cyclin B1 from Mos in terms of regulation, because it was recently shown that PKA does not exert any inhibitory effect on Mos translation induced by exogenous Mos injection (Faure et al, 1998). However, GVBD does not occur when exogenous Mos is injected in the presence of PKAc (Daar et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The hormone, therefore, triggers cyclin B1 accumulation by acting through a decrease in PKA activity (Figure 10). This again differentiates cyclin B1 from Mos in terms of regulation, because it was recently shown that PKA does not exert any inhibitory effect on Mos translation induced by exogenous Mos injection (Faure et al, 1998). However, GVBD does not occur when exogenous Mos is injected in the presence of PKAc (Daar et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Injection of the heat-stable PKA inhibitor PKI induces M-phase entry in the absence of progesterone. PKA inhibits both branches of the pathway: (i) PKA prevents synthesis of Mos and can block Mos-induced oocyte activation, and (ii) PKA blocks steps leading to activation of cdc25 (20)(21)(22)(23)(24)(25). However, no direct targets of PKA have been identified in this pathway.…”
mentioning
confidence: 99%
“…For example, purified bovine PKAc can inhibit the maturation induced by injection of Mos protein kinase (13) and also blocks Mos accumulation in response to progesterone (14). However, PKAc does not block the synthesis of endogenous Mos when mitogen-activated protein kinase (MAPK) is previously activated by injection of recombinant Mos protein (15), consistent with the observation that MAPK activity is required for full stimulation of Mos translation (16,17). Elevation of endogenous PKA activity by treatment of oocytes with 3-isobutyl-1-methylxanthine can also delay Cdc2͞cyclin B activation and germinal vesicle breakdown (GVBD) induced by injection of recombinant cyclin B or Cdc25A proteins (12).…”
mentioning
confidence: 99%